Hubungan Indeks Massa Tubuh Dengan Hipertensi Pada Penderita Hipertensi Di Puskesmas Kembaran 1 Banyumas - Amin Susanto (Viva Medika, 2020)
Hypertension is disease often called ‘the silent killer’ because it shows no early symptoms. One of risk factors for hypertension is obesity. One way to measure obesity scale is measuring value of Body Mass Index. The study aimed to know the correlation between Body Mass Index and hypertension. This study was descriptive study and conducted using a cross sectional method, sample selection using purposive sampling. Sample of this study was 106 respondents. The data that have been collected were processed using a computer program to be analyzed with Spearman correlation test. The result of this study showed that the majority of hypertension patients has normal body mass index. The results of the Spearman correlation test showed that there was a significant relationship between Body Mass Index and hypertension in the respondens where p = 0.001 (p <0.05 and r =0.605). It means this study conclude that there was relationship between Body Mass index and hypertension.